The Impact of Artificial Technology on Authors of a Cinematographic Creation - Radetzky, Michael Alexander (Faculty of Law, Hasanuddin University, 2024)
Algorithmic systems are used almost everywhere in our everyday lives and have strongly made their indispensable way into the film industry. This new reality has changed the rigid entertainment business models and has significantly impacted copyright law. The critical question that arises is how cinematographic authorship rights are affected by artificial contributions. Consequently, the main issue at hand is determining the legal status of the film author when it comes to using artificially created works. Since the film is a collectively created work of art, the possible authors were first determined by reviewing the relevant regulations. During this analysis, it has been revealed that an artificially created effort that lacks human creative participation is not considered a contribution and, consequently, not an author in the dogmatic copyright systems. This opens Pandora's box about the philosophical question of whether an artificial intelligence can or must be equated with a natural person if the creative cognitive processes are like those of a human being. Despite correct approaches, the well-intentioned proposals of the legal systems examined need to be revised. Solutions such as the e-person, the factually attributable natural person and a particular form of fair use will be experimented with in the future. A final national and international copyright solution for filmmakers has yet to be seen on the horizon.